Entry Barriers and the Labor Market Outcomes of Incumbent Workers: Evidence from a Deregulation Reform in the German Crafts Sector - Philipp Lergetporer; Jens Ruhose; Lisa Simon (Center for Economic Studies and ifo Institute (CESifo), 2018)
We study the labor market outcomes of a deregulation reform in Germany that removed licensing requirements to become self-employed in some occupations. Using longitudinal social security data, we implement a matched difference-in-differences design with entropy balancing to account for observable characteristics and unobserved individual heterogeneity. The reform tripled the number of businesses within ten years and led to slower earnings growth and higher unemployment for incumbent workers in deregulated occupations. However, the reform effect seems rather small, which we attribute to the relatively low competitiveness of new businesses. Supporting this view, the reform did not lead to overall employment growth.
Keywords: J31; J24; L11; 330; deregulation; entry barriers; self-employment; labor market outcomes; entropy balancing; matched difference-in-differences